An Analysis of the Activity of Science Textbook with reference to Science Process Skills - Singh, Shweta; Singh, Sunita (JOURNAL OF INDIAN EDUCATION, 2019)
Science has taken a very important place in this modern era when democratic societies are demanding science education for the upcoming generations. To fulfill the needs of the nation and society, NCERT has been continuously updating the curriculum of school education by modifying the patterns from subject centered to child and activity centered. National Curriculum Framework is also trying to prepare curriculum and textbooks according to students’ needs and interests. In the textbooks, sufficient activities are provided to connect science with daily life. Keeping in mind the above points, this study is conducted to analyse the nature and effectiveness of the activities, given in NCERT’s 9th grade science textbooks. The study also focuses on analysing how the science process skills have been incorporated within these activities. Purposive sampling technique is used for selecting the sample chapters. The study reveals that the activities contain basic science process skills in a representative way and that most of the activities are given in an operant form while some activities are supplemented by non-operant form. The researcher did not find a single activity which is totally in non-operant form. The presentation of each activity is simple and all the processes are explained step by step. However, the figures and charts given in these textbooks are blurred and not clear.